2019
DOI: 10.1021/acs.analchem.8b05928
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Diabetes Monitoring through Continuous Analysis of Sweat Using Flow-Through Glucose Biosensor

Abstract: We propose monitoring of diabetes through continuous analysis of undiluted sweat immediately after its excretion using a flow-through glucose biosensor. The used biosensors are based on Prussian Blue and glucose oxidase immobilized in perfluorosulfonated ionomer or gel of alkoxysilane; the resulting sensitivity with the latter reaches in batch mode 0.23 A M–1 cm–2, and the calibration range is from 1 μM to 1 mM (flow-through mode). On the basis of the glucose tolerance test known to be a clinically relevant pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(109 citation statements)
references
References 33 publications
0
106
0
3
Order By: Relevance
“…c) The relation between iontophoretic sweat and blood glucose levels in healthy subjects (sweat measurements were obtained from glucose sensor). Reproduced with permission . Copyright 2019, American Chemical Society.…”
Section: Flexible Amperometric Sensors Based On Enzymatic Electrodesmentioning
confidence: 99%
“…c) The relation between iontophoretic sweat and blood glucose levels in healthy subjects (sweat measurements were obtained from glucose sensor). Reproduced with permission . Copyright 2019, American Chemical Society.…”
Section: Flexible Amperometric Sensors Based On Enzymatic Electrodesmentioning
confidence: 99%
“…The sweating stimulation through electrophoresis of pilocarpine has been chosen because, first, it does not change the sweat lactate content during the exercise and, second, after such activation lactate concentration in sweat is independent of the rate of sweating . Moreover, using continuous diabetes monitor reported in, we have shown that after pilocarpine activation the rate of sweating retains at a constant level within 30 minutes (Figure S1, Supporting Information), which is enough for the exhaustive incremental exercise.…”
Section: Figurementioning
confidence: 99%
“…Concerning suitability of the above correlation (r>0.8, Figure ) for diagnostics, we note that despite blood being considered as a biological liquid with undoubted diagnostic potential, the lactate content in different vessel systems varies significantly. As we have reported recently, variation rates of lactate concentration upon exhaustive physical exercise for vein and capillary blood display similar Pearson correlation coefficient (0.8), but the regression line passes far from the origin. Hence, the observed correlation between the variation rates of lactate concentration in sweat (thigh, working muscle area) and blood (Figure ) is sufficient for diagnostics.…”
Section: Figurementioning
confidence: 99%
“…Such devices adopt both amperometric and potentiometric measurement systems-for lactate and glucose detection and for electrolyte detection, respectively. Since then, development of various types of totally integrated wearable sweat sensors have progressed to take the form of tattoo films, [86][87][88][89][90] wrist bands, [91][92][93] eye glasses, 94 head bands, 95 underwear, [96][97][98] and socks. 99 Although these sensors can detect analytes in sweat when the sensing elements are exposed to sweat, the detected sweat components are left in the same area and their concentration might increase as more sweat is secreted.…”
Section: Sweat Biomarkers and Their Collection/ Detection Techniquesmentioning
confidence: 99%